Dynamics and consequences of spliceosome E complex formation - Joshua Donald Larson; Aaron A Hoskins (eLife, 2017)
The spliceosome must identify the correct splice sites (SS) and branchsite (BS) used during splicing. E complex is the earliest spliceosome precursor in which the 5' SS and BS are defined. Definition occurs by U1 small nuclear ribonucleoprotein (snRNP) binding the 5' SS and recognition of the BS by the E complex protein (ECP) branchpoint bridging protein (BBP). We have used single molecule fluorescence to study Saccharomyces cerevisiae U1 and BBP interactions with RNAs. E complex is dynamic and permits frequent redefinition of the 5' SS and BS. BBP influences U1 binding at the 5' SS by promoting long-lived complex formation. ECPs facilitate U1 association with RNAs with weak 5' SS and prevent U1 accumulation on RNAs containing hyperstabilized 5' SS. The data reveal a mechanism for how U1 binds the 5' SS and suggest that E complex harnesses this mechanism to stimulate recruitment and retention of U1 on introns.